Case Report: Diffuse Lumbar Hyperostosis Causing Vertebral Canal Stenosis in a Dog With Concurrent Multicentric T-Cell Lymphoma - Foreman, Max; Belmudes, Audrey; Villiers, Elizabeth; Scarpante, Elena (Frontiers in Veterinary Science, 2022)
A 4-year-old female spayed Bullmastiff-cross presented with a 24-h history of progressive paraparesis. Neurological examination was consistent with L4–S3 myelopathy. On magnetic resonance imaging (MRI), all vertebrae showed homogenously increased short tau inversion recovery (STIR) signal with strong contrast enhancement. The vertebral canal was concentrically narrowed along the length of the L5 vertebra secondary to bony proliferation of the vertebral pedicles, dorsal lamina, and vertebral body. Cytological analysis of the peripheral lymph nodes and subsequent flow cytometry was consistent with T-cell lymphoma. The dog was euthanised due to poor prognosis. Necropsy confirmed the presence of stage V multicentric T-cell lymphoma, as well as diffuse hyperostosis of the vertebral bodies. This is the first report of presumed paraneoplastic lumbar skeletal hyperostosis.